THE DIFFERENCE BETWEEN HOT SMOKING AND COLD SMOKING ON THE QUALITY OF SKIPJACK (KATSUWONUS PELAMIS) KATSUOBUSHI - Frayogo, Dede Fyonadli; Mus, Sukirno; Leksono, Tjipto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractThis study aimed to compare the quality of katsuobushi skipjack processed by using hot smoking and cold smoking methodsin katsuobushiprocessing. The method used in the research was comparative experimental method to compare the application of method of hot smokingin temperature of 80-1000C until the decrease of fish weight â‰¤ 30% and cold smokingin temperature of 40-500C until the decrease of fish weight â‰¤ 30%. The data obtained was analyzed by using the T-test.The results showed thatkatsuobushi produced by cold smokingprocess had higher values rather than those produced by hot smoking and showing significantly different value in aroma, texture, taste, moisture content, phenol content and pH, butnot significantlydifferent in appearance and ash content. The total number of bacteria colonies on the katsuobushi produced by applying hot smoking method was 4,1 x 103cfu/g and in that applying cold smoking was 3,7 x 103cfu/g. The molds grown in both katsuobushiwas Aspergillus sp.Â Keywords:katsuobushi, skipjack, smoking